2015
DOI: 10.2147/ijn.s92019
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the macrophage inflammatory activity by TiO2 nanotubes via inhibition of MAPK and NF-κB pathways

Abstract: Biomaterial implantation in a living tissue triggers the activation of macrophages in inflammatory events, promoting the transcription of pro-inflammatory mediator genes. The initiation of macrophage inflammatory processes is mainly regulated by signaling proteins of mitogen-activated protein kinase (MAPK) and by nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathways. We have previously shown that titania nanotubes modified Ti surfaces (Ti/TiO 2 ) mitigate the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…9 Yu et al demonstrated that, compared with the small-diameter TNT specimen, the cellular behavior of large-diameter TNT specimens was better under high oxidative stress. 40,41 Similarly, in this study, under high-glucose conditions, the TNT surface with a diameter of approximately 80 nm provided good biocompatibility and osteogenetic ability compared with the SLA surface.…”
Section: Discussionsupporting
confidence: 62%
“…9 Yu et al demonstrated that, compared with the small-diameter TNT specimen, the cellular behavior of large-diameter TNT specimens was better under high oxidative stress. 40,41 Similarly, in this study, under high-glucose conditions, the TNT surface with a diameter of approximately 80 nm provided good biocompatibility and osteogenetic ability compared with the SLA surface.…”
Section: Discussionsupporting
confidence: 62%
“…As is well known, in addition to RAGE, AGEs can bind with several other receptors such as AGE-receptor complex, scavenger receptor, and Toll-like receptor 4 (TLR-4) to transmit messages [ 24 , 25 ]. Furthermore, besides NF κ B pathway, MAPK and STAT signaling have been proven to be implicated in driving inflammatory response in macrophages [ 26 , 27 ]. Therefore, RAGE/NF κ B signaling is just one of the many pathways mediating the inflammatory response induced by AGEs; other potential pathways remain to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK rapidly responds to a variety of extracellular stimuli and regulates essential cellular events to control a vast array of physiological processes, including macrophage-mediated inflammatory responses [13,14]. The MAPK signaling pathway, involving extracellular signal regulated kinase 1/2 (ERK1/2), c-Jun N-terminal protein kinase (JNK), and p38, is activated by sequential phosphorylation events, and mediates signaling cascades leading to the activation of various transcription factors, such as NF-κB [15,16].…”
Section: Introductionmentioning
confidence: 99%